Beyond the Camera: A Case Study on Students Doing Online Class and Tasks at Home - Nimes, Joderon P. (Future Science / FSH-PH Publications, 2023)
Typical learning usually happens inside the classroom setting and having face-to-face interactions with their teachers. However, when the pandemic starts to spread, the Department of Education (DepEd) announces that education will continue through online learning. In this time of dilemma, some people are not competent enough to achieve homework and chores simultaneously. Their time management and dividing the time into a particular task is already time-consuming. This study intended to determine how senior high school students in Tondo High School handle their school tasks while in their home and also to diagnose the student's ability to utilize and manage their time, discover their methods and strategies to deal with their different responsibilities, and spot what are the effects of this set-up to the students amidst the pandemic. The researchers gathered the results by conducting an online survey in a well-mannered way through Google Forms. The students involved in the study have voluntary participation. The participants described and their experiences in the new learning system and explained their difficulties and struggles in managing their school works and obligations at home. They also included the strategies they acquired to cope up with their situation. The results of the conducted study justified that many students are having a hard time dealing with the new learning system. Such poor implementation of the learning system also exhibits poor learning effectiveness to students. Handling the new learning system and managing the responsibilities and time for school affect family engagement and the personal health of the students.